Effect of vitamin A and mineral administration on the induction of oestrus in anoestrus Frieswal and Sahiwal heifers - MATHUR, A K; SRIVASTAVA, S; TYAGI, S; MANDAL, D K (The Indian Journal of Animal Reproduction, 2005)
The study was conducted on 15 Frieswal and 8 Sahiwal anoestrus heifers having mean age of 27.5 and 27.4 months,respectively. These animals were administered vitamin-A @ 6 lac IU per week for 2 weeks and Tonophosphan @ 2g/heifer for 5alternate days. Eighty percent heifers in Frieswal and 66.6% heifers in Sahiwal exhibited oestrus after 10.25 and 21.00 days oftreatment, respectively. Analysis of data revealed that treatment had a significant (p
Keywords: Anoestrus; estrus cycle; vitamins; conception rate; heifers